Da Shakespeare a Verdi, dalle traduzioni ai libretti (Comparatismi, 2025)
The article aims to explore the complex relationship between Verdi's librettos and Shakespeare's translations in nineteenth-century Italy, a field that remains largely unexplored, mainly due to the absence of a complete chronology of the editions in circulation on the peninsula in the nineteenth century. It is precisely the lack of an exhaustive catalogue that makes it difficult to trace translation choices and identify reference editions, textual variants and the preferences of librettists, who often preferred specific translators in relation to their linguistic and cultural characteristics. A case in point is the gestation of King Lear, a project never completed by Verdi, which reveals through the two versions of Antonio Somma's libretto how Shakespeare's translations influenced dramaturgical and compositional choices, and how the lack of a definitive version contributed to the failure of the attempt. By analysing the differences between the two versions of the libretto, it is possible to trace the translations used and assess how they shaped the text and the perception of the opera in Italy. The research therefore highlights the importance of a historical and philological reconstruction of the editions in order to better understand the relationship between translations and Verdi's poetics, highlighting how textual variations influenced the reception and development of Verdi's melodrama based on Shakespeare.
Keywords: Editions; Librettos; Opera; Traslations